The temporal involvement of the left supramarginal gyrus in planning functional grasps: A neuronavigated TMS study. (February 2019) - Potok, Weronika; Maskiewicz, Adam; Króliczak, Gregory; Marangon, Mattia
Abstract: The left supramarginal gyrus (SMG) is a critical structure in tool use actions, including such simple acts as selection of appropriate grasps and, if necessary, their on-line corrections. Yet, its temporal contribution to initial planning of functional grasps of tools is largely unknown. We used MRI-guided, event-related transcranial magnetic stimulation (TMS) to determine the time point when SMG involvement in processing of tools for functional grasp decision was affected most. In Exp. 1, with 15 participants, triple-pulse (10 Hz) TMS was applied to either the left anterior-to-mid SMG (amSMG; subdivisions PFt/PF) or vertex at three different time points: starting from 17 ms (i.e., delivered at 17/117/217 ms), 117 ms (117/217/317 ms) or 217 ms (217/317/417 ms) after stimulus onset. In Exp. 2, with 12 participants, we applied single-pulse TMS to either left amSMG or the left rostral middle frontal gurus (rMFG; area 46) at these same time points relative to stimulus onset. Subject- and item-based analyses of response times (RTs) were performed. Whereas the amSMG and vertex stimulation with triple pulse has revealed differential effects on RTs in general, as well as on tool orientation processing, it gave only vague pointers as to their temporal contributions to the task. Yet, amSMG and rMFG stimulation with single pulse demonstrated that, while the processing in both of these areas can be enhanced at 17 ms and no doubt at 117 ms (as compared to 217 ms), the earliest stimulation facilitated amSMG (vs. rMFG) contribution, and the latest stimulation had the opposite effect, facilitating rMFG (vs. amSMG) contribution to planning functional grasps. These outcomes demonstrate that the critical role of SMG in tool-related actions can be invoked substantially earlier than previously thought. Graphical abstract: Image 1